STRATEGI PENDIDIK DALAM MENANAMKAN NILAI-NILAI ANTI KEKERASAN PADA ANAK USIA DINI - Ariyanti, Wulan; Sulistiawati, Siti; Hidayah, Annisa Mustikhatul; Wulandari, Dini; Khotijah, Siti; Magfirah, Febry; Wahyuningsih, Tri (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2025)
Instilling anti-violence values is important to be done from an early age. This study aims to analyze educators' strategies in instilling anti-violence values in early childhood in Al-Kautsar Kindergarten, Samarinda. This research uses a qualitative method of case study research, through observation, interviews, and documentation. This research involved 2 educators and 10 students. The results of the study showed that educators applied three main strategies: audio-visual media in the form of educational videos, storytelling methods using picture storybooks, and positive habituation that was applied repeatedly. These three strategies are effective in building children's character to avoid violent behavior, both verbal and physical. Educators act as facilitators, guides, and role models who create a conducive learning environment and provide examples of positive behavior. These strategies not only increase children's awareness of anti-violence values but also form sustainable positive habits in daily life. Educators' strategies are important in instilling anti-violence values in children and it is hoped that this research can be a reference in instilling anti-violence values in early childhood.